Reflecting on a Possible Quadratic Wormhole Between Quantum Mechanics and Plurality - Freedman, Michael; Fabinger, Michal; Weyl, E. Glen (RadicalxChange, 2022)
In parallel with this blog post, we are releasing a formal paper, the results of which we will reflect on here. This project resulted from two convergent motivations. One of us recently blogged [Freedman, 2022] about a mechanism for public goods funding, Quadratic Funding (QF), proposed by another of us [Buterin et al., 2019], based on the square of the sum of square roots of individual funding contributions. A friend, Adam Brown, asked if there was a connection to the Born rule in Quantum Mechanics (QM), where a similar procedure is applied to the complex amplitudes (viz. probability amplitudes) to derive the observable probabilities of events.